PENENTUAN STRATEGI UNTUK MENCIPTAKAN KEUNGGULAN BERSAING PADA PESONA BATIK MADURA - Islamiah, Rifatul; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out the application of the SWOT analysis as the formulating strategy to create a competitive advantage at Pesona Batik Madura. This research has been conducted by using qualitative method which performs observation, interviews, and documentation. The results are then analyzed by using the SWOT analysis method whichconsists of identifying strengths and weaknesses by using the IFAS matrix and to identify opportunities and threats by using the EFAS matrix. Pesona Batik Madura has greater strengths than weaknesses which is shown in the IFAS matrix whereas the threats that is experienced the company is larger than the opportunitiesthat is shown by the EFAS matrix. Moreover,by using ST strategy (Strength Threats Strategies) companies can combine the differentiation strategy. Based on the result of the SWOT analysis and strategy formulation, it can be concluded that the differentiation strategy has made the percentage of sales increases in each month and customers are satisfied with the services which have been provided. So that companies can be more superior in the batik business competition by applying the SWOT analysis.Keywords: SWOT analysis, SWOT matrix, IFAS, EFAS, differentiation strategy.